Rural subsidizes and revealing moral hazards - Balomenou Chrysanthi; Maliari Marianthi; Semasis Simeon; Mamalis Spyridon; Pavlidis Stavros (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2019)
Purpose: At the end of the year 2013, the Greek Government to encourage the establishment of new enterprises in the agrifood sector announced the application of the program 'New Farmers Installation within the financial framework of CAP'. As a consequence, almost 8.000 young people benefited from this program as they received subsidizes up to 20.000 exteuro to establish a new agro enterprise. This work focuses on the examination of the results concerning those new entrants' enhancing of production of agro-products. Moral hazards have been created as some of them take advantage of the inefficacy of the program's control procedures and they contribute almost nothing to the final agro product. Design/methodology/approach: The paper is divided to into 2 parts. The literature of the theoretical perspective of the Greek economy is extensive. Taking under mind that Greece is a part of the European Union on the theoretical part are examined CAP's subsidizes consequences on Greek Agriculture. Then the 'New farmers' installation' program is briefly presented. The theoretical part ends with references to moral hazards creation and corruption in Greece. In the second part, the empirical results presented. The research took place during September 2016 using a formalized questionnaire. The statistical analysis included the estimation of frequencies, percentages, and means, as well as coefficient correlations. Finding: According to the findings, it has been supported that financial programs directed to agriculture should be monitored for disbursement. Otherwise, these programs cannot achieve their targets such as the increase of in productivity in the agricultural sector. Moreover, the results of the study are similar to previous researches as Moral Hazards have been created. Research limitations/implications: Taking for granted that the lack of strict controls over the disbursement contributed to the increase in moral hazards, it is proposed that providing subsidies should be accompanied with disbursements only after strict controls. It is also suggested a combination as providing subsidies should only take place on the grants that the amount spent exclusively for rural enterprise liabilities Originality/value: This paper provides the impetus for the study of moral hazard on rural subsidizes and constitutes primary research.
Keywords: Q14; 330; Financial Marketing; CAP; New farmers; Serres; Greece